Toward an intelligent high frequency AC distributed power system - Part I: conceptual design - Luk, Patrick Chi-Kwong; El-Hasan, T. S. (Praise Worthy Prize, 2016)
High frequency AC (HFAC) distributed power systems (DPS), where electric power is delivered at up to multi-kHz via cables, is an alternative means to conventional centralized power systems. When armed with on-line data, the HFAC DPS can perform intelligent management of power flow and lends itself to a host of emerging applications. The key enabling feature to realizing intelligent management in the DPS is the creation of a communication framework that allows the various sources and loads in the system to communicate their status seamlessly with each other. Whilst data communication over conventional power grid lines has been routinely implemented, there is remarkably no evidence of similar development in DPS where potential benefits would be significant. One key challenge is that DPS systems invariably operate at high frequency, thus squeezing allowable bandwidths for data. This paper explores the means by which real-time information can be achieved without installing additional physical communication channels on an existing 50 kHz current-fed HFAC DPS in lighting applications. A communication protocol is methodologically developed to facilitate robust and efficient inter-device real-time communication. The conceptual design of an intelligent HFAC DPS is proposed and the fundamental requirements and communication challenges of the modem are presented.
Keywords: Modems; Data Communication; Intelligent Power Distribution; Energy Management; Power Distribution Systems; High Frequency AC; Lighting Systems